Inhibition of smooth muscle contraction and platelet aggregation by peptide 204-212 of lipocortin 5: an attempt to define some structure requirements - K. G. Mugridge; C. Becherucci; L. Parente; M. Perretti (Hindawi Limited, 1993)
Peptide 204-212 of lipocortin (LC) 5 inhibited porcine pancreatic phospholipase A2 (PLA2) induced rat stomach strip contractions and ADP induced rabbit platelet aggregation in a concentration dependent manner (IC30 of 10 μM and 400 μM, respectively). The first two amino acids are not necessary since the eptapeptide 206-212 was equipotent in both assays (IC30 of 12.5 μM and 420 μM). Of the two pentapeptides 204-208 and 208-212 only the latter showed inhibitory activity in both models although the potency was much reduced (IC30 of 170 μM and 630 μM) compared with that of the parent nonapeptide. Comparison of peptide 204-212 effects with those of its analogues on LC1 and LC2 indicate that lysine 208 and aspartic acid 211 are essential in order to maintain a fully active nonapeptide.